Impact of Herbal Medicines like Nigella sativa, Trigonella foenum-graecum, and Ferula asafoetida, on Cytochrome P450 2C11 Gene Expression in Rat Liver - Korashy, H. M.; Al-Jenoobi, F. I.; Raish, M.; Ahad, A.; Al-Mohizea, A. M.; Alam, M. A.; Alkharfy, K. M.; Al-Suwayeh, S. A. (Drug Research, 2015)
Aim: Combined use of herbs and drugs may result in clinically important herb-drug interactions. The majorities of these interactions are thought to be metabolism-based and involve induction or inhibition of cytochrome P450 (CYP). The current study was designed to investigate the effect of some commonly used herbs on rat CYP2C11 gene expression and metabolic activity.Methods: Wistar rats were treated for 7 days with increasing doses of 3 herbs; Nigella sativa, Trigonella foenum-graecum, and Ferula asafoetida. Thereafter, CYP2C11 mRNA and protein levels were determined by real-time polymerase chain reaction (RT-PCR) and western blot analyses, respectively. In vitro metabolic activity of CYP2C11 was performed on rat hepatic microsomes using tolbutamide as specific substrate.Results: Our results showed that all the 3 herbs significantly inhibited the mRNA and protein expression levels of CYP2C11 in a dose-dependent manner. Furthermore, the in vitro enzyme metabolic activity study showed a significant decrease in the formation of 4-hyroxy-tolbutamide, a tolbutamide metabolite, at the higher doses. The inhibitory effects of the investigated herbs on rat CYP2C11 was in the order: Nigella Sativa > Trigonella foenum-graecum > Ferula asafoetida.Conclusions: The 3 herbs are strong inhibitor of CYP2C11 expression, which can lead to an undesirable pharmacological effect of clinically used CYP2C11 substrate drugs with a low therapeutic index.
Keywords: CYP2C; gene expression; herb-drug interaction; rat microsomes